Evidence of avian influenza virus in seabirds breeding on a Norwegian high-Arctic archipelago - Lee, Megan Marie; Jaspers, Veerle L.B.; Gabrielsen, W. Geir; Munro Jenssen, Bjørn; Ciesielski, Tomasz Maciej; Mortensen, Åse-Karen; Lundgren, Silje Strand; Waugh, Courtney A. (BMC Veterinary Research, 2020)
Background Wild aquatic birds serve as the natural reservoir for avian influenza virus (AIV), a disease with significant implications for avian and mammalian health. Climate change is predicted to impact the dynamics of AIV, particularly in areas such as the Arctic, but the baseline data needed to detect these shifts is often unavailable. In this study, plasma from two species of gulls breeding on the high-Arctic Svalbard archipelago were screened for antibodies to AIV. Results AIV antibodies were found in black-legged kittiwake (Rissa tridactyla) samples from multiple years, as well as in glaucous gulls (Larus hyperboreous) samples. Conclusions Despite small sample sizes, evidence of exposure to AIV was found among Svalbard gulls. A wider survey of Svalbard avian species is warranted to establish knowledge on the extent of AIV exposure on Svalbard and to determine whether active infections are present. publishedVersion